Chemoselective Probe Containing a Unique Bioorthogonal Cleavage Site for Investigation of Gut Microbiota Metabolism. (20th September 2018) - Garg, Neeraj; Conway, Louis P.; Ballet, Caroline; Correia, Mario S. P.; Olsson, Frida K. S.; Vujasinovic, Miroslav; Löhr, J.‐Matthias; Globisch, Daniel
Abstract: While metabolites derived from gut microbiota metabolism have been linked to disease development in the human host, the chemical tools required for their detailed analysis and the discovery of biomarkers are limited. A unique and multifunctional chemical probe for mass spectrometric analysis, which contains p ‐nitrocinnamyloxycarbonyl as a new bioorthogonal cleavage site has been designed and synthesized. Coupled to magnetic beads, this chemical probe allows for straightforward extraction of metabolites from human samples and release under mild conditions. This isolation from the sample matrix results in significantly reduced ion suppression, an increased mass spectrometric sensitivity, and facilitates the detection of metabolites in femtomole quantities. The chemoselective probe was applied to the analysis of human fecal samples, resulting in the discovery of four metabolites previously unreported in this sample type and confirmation of the presence of medically relevant gut microbiota‐derived metabolites.